Evaluation of the STEM Practices: The Science Courses of Inclusive Students - YILDIRIM, MEHTAP (ANKARA UNIV, FAC EDUCATIONAL SCIENCES, 2020)
This research is a case study that aims to evaluate the skills, which are performed in STEM practices, of the students with SENs in the resource rooms where science courses are taught. The study group consists of three 7th grade students with SENs. Data collection tools include content knowledge test, checklist, material evaluation form, STEM skills rubric, self-evaluation form, and semi-structured interview form. The data analysis methods involve descriptive analysis and content analysis. Findings show that the students are able to transfer their science knowledge into practice through current materials. However, they can't associate with knowledge of mathematics, technology, and engineering. In addition, it was observed that students were planning their designs in their minds but could not concretely drawing on paper. Nevertheless, it was determined that they were able to realize their designs. The result of this research has suggested that inclusive students should be integrated into STEM practices.
Keywords: Inclusive students; STEM practices; students with special needs; special education; resource rooms; science courses; AUTISM SPECTRUM DISORDER; TEACH NUMERACY SKILLS; EXPLICIT INSTRUCTION; SCHOOL-STUDENTS; ADDITION FACTS; MODERATE; CHILDREN; DISABILITIES; CURRICULUM; MATHEMATICS